Immigrant labour in Europe in times of crisis and austerity: An international political economy analysis. (April 2015) - Pradella, Lucia; Cillo, Rossana
This article develops an international political economy analysis of immigrant labour in Western Europe, with a focus on Italy and the UK in the period following the outbreak of the global economic crisis in 2008. Seeking to overcome the problem of methodological nationalism, the article places cross-national comparison against the backdrop of the broader process of international accumulation of capital. In this light, it examines the causes of the differential effects of the economic crisis upon EU member states and various sections of the workforce. In both the UK and Italy, labour conditions and trade unions are under attack; immigrant workers have been particularly affected by the rise in levels of unemployment, the worsening of working conditions, and the heightening of anti-immigration practices, legislations and discourses. The article concludes with a discussion of how the main trade unions in the UK and Italy are responding to these economic, social and political challenges.